2015
DOI: 10.1186/s12917-015-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

International veterinary epilepsy task force consensus proposal: diagnostic approach to epilepsy in dogs

Abstract: This article outlines the consensus proposal on diagnosis of epilepsy in dogs by the International Veterinary Epilepsy Task Force. The aim of this consensus proposal is to improve consistency in the diagnosis of epilepsy in the clinical and research settings. The diagnostic approach to the patient presenting with a history of suspected epileptic seizures incorporates two fundamental steps: to establish if the events the animal is demonstrating truly represent epileptic seizures and if so, to identify their und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
379
1
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(422 citation statements)
references
References 47 publications
13
379
1
29
Order By: Relevance
“…Dogs with IE were required to fit Tier I or Tier II confidence level of IE diagnosis (De Risio and others 2015). In brief, Tier I dogs had a history of two or more epileptic seizures with unremarkable interictal physical and neurological examination with normal bloodwork and urinalysis.…”
Section: Methodsmentioning
confidence: 99%
“…Dogs with IE were required to fit Tier I or Tier II confidence level of IE diagnosis (De Risio and others 2015). In brief, Tier I dogs had a history of two or more epileptic seizures with unremarkable interictal physical and neurological examination with normal bloodwork and urinalysis.…”
Section: Methodsmentioning
confidence: 99%
“…They arise through disturbances in forebrain function and can be caused by metabolic derangements, by genetic or acquired abnormalities in neuronal function or by structural brain disease (Berg and others 2011, Muñana 2013, Finnerty and others 2014, Pakozdy and others 2014, Wahle and others 2014, Berendt and others 2015). The diagnostic approach to cats with epileptic seizures includes complete physical and neurological examinations, analysis of various biochemical and haematological parameters, advanced imaging of the brain and analyses of cerebrospinal fluid (CSF) when appropriate (Rusbridge 2005, Smith Bailey and Dewey 2009, De Risio and others 2015). …”
mentioning
confidence: 99%
“…An increased likelihood of a significant brain lesion with age has been established in neurologically normal dogs with recurrent seizures, and studies have indicated a substantially higher risk in dogs older than six years of age, which is primarily related to the higher prevalence of neoplastic lesions in older animals (Smith and others 2008, Schwartz and others 2013, Armasu and others 2014, De Risio and others 2015). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the presumptive diagnosis of primary epilepsy, all dogs met the requirements of the tier I confidence level by De Risio, besides laboratory tests being performed on each dog (De Risio et al, 2015).…”
Section: Subjectsmentioning
confidence: 99%